VD_FINDINFO ML / 2019 / 14 vom 28. Dezember 2018 - VD Tribunal cantonal (2018)
MAINLEVÉE DÉFINITIVE, TITRE DE MAINLEVÉE, DÉPENS, INTÉRÊT MORATOIRE, DÉCISION EXÉCUTOIRE | 80 al. 1 LP, 106 al. 1 CPC (CH), 111 al. 2 CPC (CH), 95 al. 1 let. b CPC (CH), 95 al. 3 let. b CPC (CH), 6 TDC